The Problem of Social Protection of the Interests of Families Raising Children With Disabilities of Health and Children with the Limited Possibilities of Health - Kalashnikova, Lyudmila (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The issues of social security for children with disability acts as the most sensitive indicator of quality of life, integrating all the negative sides of modern society and vividly describing the effectiveness of all social institutions, including government authorities, public associations, aimed at creating conditions under which people with special needs can lead an independent life and to participate actively in all its aspects. Achieving significant progress in the implementation of the policy in relation to children with disabilities is impossible without knowledge of the needs of the families in which they are raised, as well as assessing the quality of services provided to these families. The article presents the results of a poll of parents of children with disabilities and children with disabilities, with the support of the Nikolayev regional support movement of people with disabilities are «Strong together» and the Department of labour and social protection of population of the Nikolayev city Council in january-may 2018 in the city of Nikolayev. Its main objective was to identify the major obstacles to ensure the social safety of this category of population. In particular, the analysis of the opinions and judgments of parents about the difficulties they encounter in daily life, the quality of provision of medical, social, educational services, visiting rehabilitation institutions, the organization of leisure of their children, as well as the definition of acceptable types and forms of education for children with disabilities different groups of diseases. For the basis of the empirical data, the generalizations about the state of social protection rights to a decent life for children with disabilities and develop practical recommendations.